2018
DOI: 10.1111/raq.12291
|View full text |Cite
|
Sign up to set email alerts
|

Starch gelatinization on the physical characteristics of aquafeeds and subsequent implications to the productivity in farmed aquatic animals

Abstract: Starches are added macronutrients in aquafeeds to act as binders and provide inexpensive digestible energy to aquatic animals. These qualities can be further enhanced through gelatinization, which occurs when the crystalline region of amylopectin within the starch granule melts along with the leaching of amylose to form a gel matrix. This process readily occurs in the presence of heat and water, and therefore, some degree of starch gelatinization is ubiquitous in aquafeeds. When using simple technology, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 75 publications
1
28
0
Order By: Relevance
“…These results might be attributed to some benefits of the extrusion process. For example, the high‐temperature processing process of extruded diets may lead to high starch gelatinization, loose structure of protein, and degradation of some heat‐labile antinutritional factors, all of which could be conducive to the digestion and absorption of dietary protein and other nutrients for aquatic animals (Singh et al 2007; Glencross et al 2011; Romano and Kumar 2019). On the other hand, the processing conditions such as the high temperature, high humidity, and high pressure of the extruded diets might reduce the concentrations of harmful microorganisms and improve the health of the animals (Kelley and Walker 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results might be attributed to some benefits of the extrusion process. For example, the high‐temperature processing process of extruded diets may lead to high starch gelatinization, loose structure of protein, and degradation of some heat‐labile antinutritional factors, all of which could be conducive to the digestion and absorption of dietary protein and other nutrients for aquatic animals (Singh et al 2007; Glencross et al 2011; Romano and Kumar 2019). On the other hand, the processing conditions such as the high temperature, high humidity, and high pressure of the extruded diets might reduce the concentrations of harmful microorganisms and improve the health of the animals (Kelley and Walker 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that the shrimp that consumed the extruded diets also had higher α‐amylase activity in the hepatopancreas than those that consumed the pelleted diets. This could be explained that high starch gelatinization caused by extrusion process improves the ability of shrimp to digest starch (Romano and Kumar 2019). Overall, these results suggested that extruded diets were conducive to the secretion of protease and α‐amylase in the hepatopancreas, thereby improving the digestion and absorption of nutrients and leading to better growth of shrimp.…”
Section: Discussionmentioning
confidence: 99%
“…This process destroys the enzyme inhibitors in the starch, shortening the starch structural chain and improving the utilization rate of starch, but this is not necessarily beneficial to fish (Li et al, 2020). And evidence indicated that gelatinization pretreatment could improve the utilization efficiency of starch in fish since the gelatinized starch is easier to be digested and absorbed (Ai & Jane, 2015; Romano & Kumar, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Starch cook increases starch digestibility and therefore has an effect on the availability of macronutrient energy, as well as the final animal composition and health status with changes in total body total lipid, crude protein, ash and moisture content possible depending on the starch source, degree of cook as well as the fish or crustacean species. 20 Some studies have shown links between starch digestibility and changes in digestive tract biochemistry which may also lead to changes in immunity and disease resistance in fish. 21 , 22…”
Section: Introductionmentioning
confidence: 99%
“…19 Starch cook increases starch digestibility and therefore has an effect on the availability of macronutrient energy, as well as the final animal composition and health status with changes in total body total lipid, crude protein, ash and moisture content possible depending on the starch source, degree of cook as well as the fish or crustacean species. 20 Some studies have shown links between starch digestibility and changes in digestive tract biochemistry which may also lead to changes in immunity and disease resistance in fish. 21,22 The use of NIR spectroscopy to predict starch cook has been successfully demonstrated previously for flour production in grain mills, [23][24][25] and applied to the extrusion of pasta for human consumption 26,27 To our knowledge, there has been no published research into the use of NIR spectroscopy for monitoring starch cook in final aquafeed products.…”
Section: Introductionmentioning
confidence: 99%